The Influence of Investment Knowledge, Income Expectations, and Service Quality on Gold Savings Investment Decisions - Paramita, Ni Luh Gede Anindya; Suarta, I Made; I Made Wijana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2026)
This study aims to analyse the influence of investment knowledge, income expectations, and service quality on gold savings investment decisions at PT Pegadaian (Persero) Tabanan Branch. The background of this study is based on the low number of active customers in gold savings transactions compared to the number of registered customers, indicating the existence of factors influencing investment decisions. This study used a quantitative method with an exploratory approach. The study population consisted of 142 customers, with respondents meeting the minimum sample criteria. Data were analysed using multiple linear regression with the aid of SPSS software. The results indicate that investment knowledge, income expectations, and service quality simultaneously influence investment decisions. However, these three independent variables partially showed no effect on gold savings investment decisions. This finding indicates that investment decisions are more influenced by a combination of factors than by the influence of each variable individually. The contribution of this study lies in strengthening the understanding that, in the context of gold savings, investment decisions are not determined by a single dominant factor, but rather by the simultaneous interaction of various factors. Furthermore, this research provides practical implications for financial institutions, particularly Pegadaian, in designing strategies to increase customer participation through a more integrated approach. This research suggests the need to develop the model by adding other variables such as financial literacy, risk perception, and social influence, as well as expanding the scope of the research locations to obtain more comprehensive results.